Этюды для левой руки: [рассказы] / Марианна Гончарова - Гончарова Марианна Борисовна (Азбука, 2015)
Экземпляры: ф.24 (20160411) / Инвентарный номер: 51540 / Цена: 292.00 / Авт.знак: Г 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6